HUBUNGAN KONSUMSI MAKANAN JAJANAN TERHADAP STATUS GIZI (KADAR LEMAK TUBUH dan IMT/U) PADA SISWA SEKOLAH DASAR (Studi di Sekolah Dasar Negeri 01 Sumurboto Kota Semarang) - Nurul Islami Dini; Siti Fatimah Pradigdo; Suyatno Suyatno (Jurnal Kesehatan Masyarakat (Undip), 2017)
Street food consumption habits in school children, is a phenomenon found in almost every school. Favorite type of food among children foods that contain high levels of fat and calories, causing obesity. This study aims to determine the relationship of street food consumption on nutritional status (body fat and BMI/U). Research conducted at Sumurboto elementary 01 Semarang. The study was conducted in May 2016. This type of research is quantitative with cross sectional approach. Total sampling were 155 children. Sampling as many 66 students by the purposive sampling technique. This researchuse the questionnaire, Food Recall, the scale weight, height measurement, SPSS and nutrisurvey programas a research instrument. Data processing with Spearman Rank test. The result show majority of subject (57.6%)  have a normal nutritional status and normal body fat category (95.5%). The test results showed that there was significant relationship between the energy content of the consumption of street food with daily energy intake (p = 0,000), significant relationship between the fat content of the consumption of street food with daily fat intake (p = 0,000), no significant relationship between daily energy intake with nutritional status (p= 0,954), no significant relationship between daily fat intake with nutritional status (p= 0,702), a significant relationship between the energy content of the consumption of street food with nutritional status (p= 0,046), a significant relationship between the fat content of the consumption of street food with nutritional status (p= 0,029). The advice given to students should be more selective in buying snacks, choose snacks in terms of nutritional value, enact regulations to the seller in the school environment in accordance with health standards.